Characteristics of soil in the areas adjacent to the ports of the Black Sea coast - M. S. Zambriborshch (Kazimierz Wielki University, 2016)
Zambriborshch М. S. Characteristics of soil in the areas adjacent to the ports of the Black Sea coast Journal of Education, Health and Sport. 2016;6(9):962-965. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.196031 http://ojs.ukw.edu.pl/index.php/johs/article/view/4047         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7                                                                                                                                      © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016.   Characteristics of soil in the areas adjacent to the ports of the Black Sea coast   М. S. Zambriborshch   Ukrainian Scientific Research Institute of Transport Medicine of Ministry of Health of Ukraine, Odessa   Abstract As a result, over the past half-century technogenesis was "pollution of the biosphere", while accumulating medium has become the soil. If the environmental assessment of the urban area one of the most informative sites is studying the soil cover, accumulating dirt that come over an extended period. The soil is the most sensitive indicator of contamination in the landscape due to its material composition and physico-chemical parameters. On the territory of the Odessa region, there are 4 major seaports of Ukraine, which are created and improved specialized complexes for processing of iron-ore concentrate, fertilizer and sulfur. Samples of soil, which took away from the areas of ports Yuzhny, Chernomorsk andOdessa, were analyzed for metals and toxic elements. Keywords: soil pollution by port territory, toxic elements, heavy metals